2014
DOI: 10.1016/j.apcata.2013.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of sunflower oil over Pt–Ni bimetallic supported catalysts: Preparation, characterization and catalytic activity

Abstract: It had been reported that in order to improve oil hydrogenation catalysts the geometric or electronic effects of the catalysts must be manipulated in order to achieve the desired activity or selectivity. To achieve this, the development of an active and selective bimetallic catalyst was undertaken. An innovative approach was taken to synthesize Pt-Ni catalysts supported on mesoporous silica using the surface redox reaction (Srr) technique.It was determined that the Srr preparation method resulted in better act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Therefore, the strength of double bonds is decreased with a decrease in the electronegativity of the metal ions in the support because the electron density of platinum particles is increased with a decrease in the electronegativity of the metal ions in support. McArdle et al proposed that the an increase in the electron donor characteristic by the addition of Ni to Pt would weaken the adsorption strength of double bonds, which result in the decrease in the TFA levels [11]. Thus, stronger hydrogen adsorption and weaker unsaturated fatty acid adsorption would result in the lower TFA levels because the half-hydrogenated intermediates are hydrogenated before the intermediates loose the hydrogen and form trans double bonds.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, the strength of double bonds is decreased with a decrease in the electronegativity of the metal ions in the support because the electron density of platinum particles is increased with a decrease in the electronegativity of the metal ions in support. McArdle et al proposed that the an increase in the electron donor characteristic by the addition of Ni to Pt would weaken the adsorption strength of double bonds, which result in the decrease in the TFA levels [11]. Thus, stronger hydrogen adsorption and weaker unsaturated fatty acid adsorption would result in the lower TFA levels because the half-hydrogenated intermediates are hydrogenated before the intermediates loose the hydrogen and form trans double bonds.…”
Section: Resultsmentioning
confidence: 97%
“…McArdle et al reported a platinum catalyst supported on mesoporous silica that had high catalytic activity and low TFA selectivity for the hydrogenation of sunflower oil [10]. In addition, they reported that the addition of nickel to Pt/SiO 2 catalyst improved the cis-isomer selectivity [11]. Hsu et al have reported a Pd/Al 2 O 3 catalyst with higher activity and lower TFA selectivity for the hydrogenation of canola oil than that for Pd/C and Pd/BaSO 4 catalysts [12].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In order to improve the sunflower oil hydrogenation, different bimetallic Pt/Ni catalysts supported on mesoporous silica were recently synthetized [19]. Experimental results show that the addition of Ni on Pt/SiO 2 catalyst produces a significant drop in the trans-formation, compared to the corresponding Pt monometallic catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Although, amount of trans fatty acids produced during the process of oil hydrogenation, depends of the activity of used catalysts (McArdle et al, 2014) optimization parameter which increases activity also leads to the increased trans content (Kemache et al, 2009;Plourde et al, 2004;Rylander, 1970).…”
Section: Rate Constants and Reaction Pathwaysmentioning
confidence: 99%